(untitled) (Acta Entomologica Serbica, 2020)
Ophraella communa LeSage, 1986 (Coleoptera: Chrysomelidae, Galerucinae) is a North American chrysomelid successfully spreading through Europe in recent years. It is a natural enemy and a potential biocontrol agent of Ambrosia artemisiifolia L., an important invasive weed, both for agricultural crops and public health (Vrbničanin, et al., 2008). In Europe, O. communa was first detected in Italy (Boriani et al., 2013), after which it has spread to Switzerland (Müller-Schärer et al., 2014), Slovenia (Seljak, 2017) and Croatia (Zadravec et al., 2019). Here we report the first record of O. commmuna from Serbia. Ambrosia artemisiifolia L. (Asteraceae) plants were surveyed during 2020 in 7 localities in Serbia (Fruška gora - Ležimir, Šid, Sremska Mitrovica, Bela Crkva, Belgrade, Donji Milanovac, Valjevo, Stara planina). Plants were surveyed in the fields, samples were gathered and then inspected in the laboratory.